2020
DOI: 10.1051/0004-6361/201937409
|View full text |Cite
|
Sign up to set email alerts
|

Non-detection of TiO and VO in the atmosphere of WASP-121b using high-resolution spectroscopy

Abstract: Thermal inversions have long been predicted to exist in the atmospheres of ultra-hot Jupiters. However, detection of two species thought to be responsible -TiO and VO -remain elusive. We present a search for TiO and VO in the atmosphere of the ultra-hot Jupiter WASP-121b (T eq 2400 K), an exoplanet already known to show water features in its dayside spectrum characteristic of a temperature inversion as well as tentative evidence for VO at low-resolution. We observed its transmission spectrum with UVES/VLT and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
94
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(105 citation statements)
references
References 142 publications
(300 reference statements)
11
94
0
Order By: Relevance
“…In order to confirm and expand upon previous detections, we present an atomic species inventory of the ultra-hot Jupiter WASP-121b, using high-resolution spectra taken with VLT/UVES (Dekker et al 2000), an instrument which has seen successful use for the exploration of exoplanet atmospheres (Snellen 2004;Khalafinejad et al 2017;Gibson et al 2019). The blue arm of these observations was previously explored by (Gibson et al 2020), and analysis of the red arm in a search for molecular features was presented in Merritt et al (2020): this paper presents analysis of both the red and blue arms combined with the aim of searching for a broad range of species. In Sec.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…In order to confirm and expand upon previous detections, we present an atomic species inventory of the ultra-hot Jupiter WASP-121b, using high-resolution spectra taken with VLT/UVES (Dekker et al 2000), an instrument which has seen successful use for the exploration of exoplanet atmospheres (Snellen 2004;Khalafinejad et al 2017;Gibson et al 2019). The blue arm of these observations was previously explored by (Gibson et al 2020), and analysis of the red arm in a search for molecular features was presented in Merritt et al (2020): this paper presents analysis of both the red and blue arms combined with the aim of searching for a broad range of species. In Sec.…”
Section: Introductionmentioning
confidence: 73%
“…At high resolution, a search for TiO or VO in the transmission spectrum of WASP-121b using UVES (UV-Visual Echelle Spectrograph) on the VLT failed to detect either (Merritt et al 2020), in conflict with earlier low-resolution work (Evans et al 2016(Evans et al , 2018Tsiaras et al 2018), though the inaccuracy of the VO high-temperature line-list was cited as a possible cause for the nondetection of VO. Analysis by Gibson et al (2020) of the same UVES transits, and by Bourrier et al (2020a) and Cabot et al (2020) using HARPS (High-Accuracy Radial-velocity Planet Searcher) on La Silla, have detected Fe deeper in the atmosphere, with Cabot et al (2020) additionally detecting the presence of H .…”
Section: Introductionmentioning
confidence: 80%
“…However, there is an ongoing debate about the role of TiO/VO in atmospheres with particularly large day-night temperature contrasts. Although previous studies have shown that these compounds are likely to be thermally dissociated on the hotter day-side, specifically for WASP-121b which has a similar (albeit slightly cooler) P -T structure than WASP-12b (Parmentier et al 2018), they may condense out of the night-side atmosphere entirely (Parmentier et al 2018;Merritt et al 2020). Furthermore, both TiO and VO are currently very difficult to detect directly (Mikal-Evans et al 2020), as this would require high resolution observations in the near-UV/optical range.…”
Section: Effects Of Tio and Vomentioning
confidence: 99%
“…This agrees with the work of Fortney et al (2008), which postulated that the presence of optical absorbers would lead to, and require, large day-night temperature contrasts. However, Merritt et al (2020) used highresolution ground-based observations to place limits on the maximum abundances of TiO and VO in the terminator of WASP-121 b to log(TiO)<−9.26 and log(VO)<−7.88. Nevertheless the authors of this study note that these upper bounds are degenerate with the cloud deck and scattering properties while also being limited by the accuracy of the VO line lists.…”
Section: Previous Claims Of Optical Absorbersmentioning
confidence: 99%